Dairy Farm Household`s Economy: Case Study at Pandesari, Pujon, Malang - Hartono, B (ANIMAL PRODUCTION, 2006)
The objective of this research was to analyze householdâs economy of dairy farms. The study was conducted at Pandesari Village, Pujon District, Malang Regency, East Java Province on August 2004. One hundred twenty five farm households were chosen as respondents using a stratified purposive sampling technique. Data was Â analyzed by using descriptive method. The results showed thatÂ  the absorbtion of family labor in dairy farmer on the first second and third scales were 226.77, 134.52 and 68.69 JKSP/UT/year, respectively. The contribution of the dairy income of the first, second and third scales wereÂ  53.70%,Â  68.38% andÂ  86,81%, respectively. The contribution of expenditure for food on the first second and third scales were 41.18%,Â  36.18% andÂ  30.18%, respectively. In conclusion dairy farms were be able to absorb family labor,Â  as theÂ  main source of household`s income and increased the life standar of farmers. (Animal Production 8(3): 226-232 (2006)Â Key Words : Dairy farm, family labor, householdâs economy